Gluon decay into heavy quark pair under a strong magnetic field - Chen Shile; Zhao Jiaxing; Zhuang Pengfei (EPJ Web of Conferences)
Due to the extreme large magnetic field produced in the initial stage of non-central heavy-ion collision, the dynamical process of gluon decay into heavy quark pair will take place under an external field rather than in vacuum. Unlike in the vacuum case, where the process is forbidden by energy momentum conservation, under the external field, a process emerges considering the background energy which recovers the conservation. We calculate the gluon decay rate at leading order under a uniform magnetic field.